2018
DOI: 10.3892/ol.2018.9814
|View full text |Cite
|
Sign up to set email alerts
|

Effect of STAT3 decoy oligodeoxynucleotides mediated by ultrasound-targeted microbubbles combined with ultrasound on the growth of squamous cell carcinoma of the esophagus

Abstract: Effect of STAT3 decoy oligodeoxynucleotides (ODN) transduced by ultrasound microbubbles combined with ultrasound on the growth of esophageal squamous cell carcinoma and its mechanism were analyzed. EC9706 cells were cultured in vitro and divided into four groups: group E (ultrasound microbubble + ultrasound irradiation), group P (liposome + ultrasound irradiation), group C (ultrasound), and group CC (ultrasound microbubbles). Mutant ODNs were used in groups E and P and the control group was group EC and PC, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A similar effect was observed in the mouse group treated with the STAT3 ODN-decoy loaded in liposomes plus ultrasonic irradiation. Still, its efficiency was lower than in the mice that received the STAT3 ODN-decoy loaded ultrasonic microbubble plus ultrasonic irradiation [202].…”
Section: Odn-decoy-based Therapeuticsmentioning
confidence: 86%
See 1 more Smart Citation
“…A similar effect was observed in the mouse group treated with the STAT3 ODN-decoy loaded in liposomes plus ultrasonic irradiation. Still, its efficiency was lower than in the mice that received the STAT3 ODN-decoy loaded ultrasonic microbubble plus ultrasonic irradiation [202].…”
Section: Odn-decoy-based Therapeuticsmentioning
confidence: 86%
“…Zhang et al investigated methods for the efficient and safe delivery of the STAT3 ODNdecoy to esophageal squamous cell carcinoma [202]. First, they considered embedding the drug into liposomes, but due to the low transfection efficiency of liposomes, they developed another method of delivering the STAT3 ODN-decoy.…”
Section: Odn-decoy-based Therapeuticsmentioning
confidence: 99%
“…Studies have reported that abnormal activation of the JAK-STAT signaling pathway can promote tumorigenesis [36] . The expression of KIRREL3 may be regulated by STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…They might decrease the tumor burden, thus either making it easier surgical resection or offering symptom relief. Microbubble-assisted ultrasound (i.e., sonoporation or sonopermeabilization) is an emerging method for the non-invasive and targeted delivery of chemotherapeutic drugs, immunotherapeutic agents, photo/sonodynamics agents, and nucleic acids into digestive cancers [8][9][10]. These therapeutics are either co-injected intravenously with microbubbles (MBs) or loaded on or into the MBs before their intravenous (i.v.)…”
Section: Introductionmentioning
confidence: 99%
“…The influence of some of these factors on the delivery of chemotherapeutics, has been investigated in murine models of digestive cancers but also in pilote clinical studies [14]. Both preclinical and clinical investigations mainly focused on colorectal, pancreatic and liver cancers [8,[15][16][17]. In this review, we provide a survey on the preclinical and clinical studies investigating the therapeutic efficacy and safety of delivery of chemotherapeutics using MBassisted US for the treatment of colorectal, pancreatic and liver cancers.…”
Section: Introductionmentioning
confidence: 99%